2018
DOI: 10.2217/fca-2018-0003
|View full text |Cite
|
Sign up to set email alerts
|

Prescribing Patterns of Oral Antiplatelets in Wales: Evolving Trends From 2005 to 2016

Abstract: This first-look analysis of real-life antiplatelet data demonstrates a decrease in the overall prescribing costs with varying patterns. This may aid policy-makers in reviewing funding strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 23 publications
1
4
0
1
Order By: Relevance
“…The declining rate since 2012 is likely attributable to emerging evidence against the use of antiplatelet agents for primary prevention of cardiovascular events, 9,10 and stroke thromboprophylaxis in atrial fibrillation 11 . This is consistent with trends reported in a population in the UK 12 …”
Section: Figuresupporting
confidence: 80%
“…The declining rate since 2012 is likely attributable to emerging evidence against the use of antiplatelet agents for primary prevention of cardiovascular events, 9,10 and stroke thromboprophylaxis in atrial fibrillation 11 . This is consistent with trends reported in a population in the UK 12 …”
Section: Figuresupporting
confidence: 80%
“…We are aware of few other studies on this topic; however, two recent studies have similarly described a temporal trend of decreasing low-dose aspirin prevalence. In Wales, Protty et al [ 11 ] found that low-dose aspirin prescription rates decreased by 15% from 2005–2016. In a study based on US National Health Interview Survey data from the United States, self-reported aspirin use dropped from 32.6% in 2015 to 30.0% in 2012, with a slighter larger drop seen for primary CVD prevention [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…There is no reason therefore why two, or perhaps all three of the preventives should not be taken for protection against vascular disease events. At the same time, it seems unfortunate that there is a marked year‐on‐year decline in the prescribing of aspirin in the UK in favor of newer and more expensive antiplatelet and antithrombotic agents, 29 for none of which is there evidence suggestive of a reduction in cancer.…”
Section: Discussionmentioning
confidence: 99%